Guhong Injection Alleviates Cerebral Ischemia–Reperfusion Injury via the PKC/HIF-1α Pathway in Rats - Yu, Li; Zhang, Yangyang; Zhao, Xixi; Wan, Haitong; He, Yu; Jin, Weifeng (Frontiers in Pharmacology, 2021)
Guhong injection (GHI) is a drug for ischemic stroke created by combining safflower, a traditional Chinese medicine, and aceglutamide, a Western medicine. In this study, we investigated the curative effect of GHI on cerebral ischemia–reperfusion (I/R) injury via the PKC/HIF-1α pathway in rats. Adult male Sprague Dawley rats were randomly divided into 7 groups: sham-operated, middle cerebral artery occlusion (MCAO), GHI, nimodipine injection (NMDP), MCAO+LY317615 (PKC inhibitor), GHI+LY317615, and NMDP+LY317615. After establishing an MCAO rat model, we performed neurological deficit testing, 2,3,5-triphenyltetrazolium chloride staining, hematoxylin and eosin (HE) staining, enzyme-linked immunosorbent assay, Western blotting, and q-PCR to detect the brain damage in rats. Compared with the MCAO group, the GHI and GHI + LY317615 group showed neurological damage amelioration as well as decreases in serum hypoxia‑inducible factor‑1α (HIF-1α), protein kinase C (PKC), and erythropoietin levels; brain HIF-1α and inducible nitric oxide synthase protein expression; and brain HIF-1α and NOX-4 mRNA expression. These effects were similar to those in the positive control groups NMDP and NMDP+LY317615. Thus, our results confirmed GHI can ameliorate cerebral I/R injury in MCAO rats possibly via the PKC/HIF-1α pathway.